Non-traditional cyanines: Candidate materials for all-optical signal processing applications - Hales, J; Matichak, J; Ohira, S; Thorley, K; Anderson, H; Brédas, J; Marder, SR; Perry, J (2009)
Development of non-traditional cyanine systems has allowed for improvements in the material properties required for all-optical signal processing applications: enhanced third-order nonlinearity, low nonlinear losses, improved processability, and controlled intermolecular interactions in the solid-state. © 2009 Optical Society of America.